Utlilizing ICT in English Language Teaching and Learning from the Perspective of Afghan EFL Tearchers - Wahidullah Alokozay; Noorullah Shadab; Rahimullah Dauodzai (Randwick International of Education and Linguistics Science Journal, 2022)
This study researched to determine Afghanistan public universities teachers’ perceptions and challenges towards ICT utilization in teaching and learning the English language. The study used a quantitative design to collect data from 50 Afghanistan public universities’ teachers through a questionnaire which was analysed through descriptive statistics (percentage, mean, standard deviation and frequency). The results of the study indicated that Afghanistan public universities teachers’ perceptions were positive towards ICT utilization in teaching and learning of the English language in spite of some major, mild and minor challenges which preclude them from using ICT in teaching. The study suggested that further research should be conducted to find out the perceptions and challenges of both private and public universities’ teachers towards ICT use in teaching and learning the English language. Finally, the finding of this study is significant for MOHE, MOE, and MOICT to integrate a successful ICT system in Afghanistan, especially in educational institutions.